Heritage Potential and Tourist Attraction of Chinese Heritage in Parakan City, Temanggung Regency - Martana, Septa Hendra; Swasto, Deva Fosterharoldas (ASTONJADRO, 2024)
Parakan City, located in Parakan District, Temanggung Regency, was the former capital of Menoreh during the Ancient Mataram period. With this historical background, there are a number of cultural heritage in Parakan. One of them is a historic building owned by the descendants of the Chinese in the form of residential houses that are still in good condition today. With the proposal of Parakan as a Heritage City by the Ministry of PUPR in 2015, it has considerable influence. One of them is the emergence of heritage tourism which has been running until now by visiting the building objects of Chinese descent. Parakan City, in Parakan Wetan to be precise, there is a Chinatown Area, proposed as a Cultural Heritage Area of ​​Temanggung Regency. This study aims to determine the heritage potential of these Chinese buildings in relation to the tourism component that currently exists. By starting to expand Heritage Tourism in Parakan, it is hoped that it will support the continuity of these heritage attractions in the future.